Role of Motivational Content on Instagram in Enhancing Generation Z’s Self-Esteem: An Empirical Analysis - Yeni Rahkmawati; Dewi Anggraini; Yuana Sukmawaty; Selvi Annisa; Muhammad Agha Putra Al Fajrin; Dwi Cahyaning Putri; Saira Aulia Ananda; Dwi Anisatun Nabilah (Information Technology and Science (ITScience), 2026)
Generation Z (Gen Z) is a generation that grew up in the digital era with intensive use of social media, including Instagram. As the largest user group, Gen Z consumes a wide range of influencer-generated content, including motivational content that may affect psychological well-being, particularly self-esteem. However, empirical studies specifically examining the influence of motivational content from Instagram influencers on Gen Z’s self-esteem remain limited. This study aims to analyze Gen Z’s interest in motivational content on Instagram and to examine changes in self-esteem before and after exposure to such content. A quantitative approach using a quasi-experimental one-group pretest–posttest design was employed. The sample consisted of 150 university students in Banjarbaru City selected through purposive sampling. Data were collected using the Rosenberg Self-Esteem Scale (RSES) administered via questionnaires. The Wilcoxon Signed-Rank Test was used to analyze differences in self-esteem scores before and after treatment. The results indicate a significant increase in self-esteem following exposure to motivational content on Instagram. The average post-treatment self-esteem score was higher than the pre-treatment score, confirming the positive impact of motivational content. In addition, although most respondents reported only occasional exposure to motivational content, the majority expressed liking and interest in such content. These findings suggest that motivational content on Instagram contributes positively to enhancing Gen Z’s self-esteem and may serve as an effective medium for psychological empowerment.